‘Messianic Fraternity’: Anticommunism in the General Conferences of the Latin American and Caribbean Episcopate - Carlos Piccone-Camere (Religions)
This paper analyzes the development and consolidation of anticommunist discourse in the General Conferences of the Latin American Episcopate (CELAM), from Rio de Janeiro to Aparecida. It adopts a critical perspective to examine the construction of the “messianic fraternity” myth—an ideological narrative contrasting Christian ideals of community and redemption with Marxist principles of class struggle and revolution, which served as a central axis for the Church’s rejection of communism in Latin America. Grounded in a critical analysis of the CELAM’s final documents, this study identifies the theological, political, and social underpinnings of this stance, situating it within the historical and geopolitical dynamics that positioned the Church as a key counterforce to Marxism in the region. It also examines how anticommunist positions shaped pastoral strategies, particularly in relation to social movements like liberation theology, and reinforced an episcopal identity centered on defending Christian values against a perceived global ideological threat. This analysis highlights the Church’s internal tensions and contradictions and the broader impact of its anticommunist stance on Latin America’s sociopolitical and religious dynamics in the twentieth century.